2023
DOI: 10.1029/2022gh000769
|View full text |Cite
|
Sign up to set email alerts
|

Modeling pH and Temperature Effects as Climatic Hazards in Vibrio Vulnificus and Vibrio Parahaemolyticus Planktonic Growth and Biofilm Formation

Abstract: Climate‐induced stressors, such as changes in temperature, salinity, and pH, contribute to the emergence of infectious diseases. These changes alter geographical constraint, resulting in increased Vibrio spread, exposure, and infection rates, thus facilitating greater Vibrio ‐human interactions. Multiple efforts have been developed to predict Vibrio exposure and raise awareness of health risks, but most models only use temperature and salinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…To our knowledge, no recent studies have evaluated the impact of salt on the adhesion and formation of biofilms by V. vulnificus. On the other hand, the study by Velez et al (2023) showed higher biofilm production by several clinical and environmental strains of V. vulnificus and V. parahaemolyticus at acidic pH values. Çam and Brinkmeyer (2020) confirmed these observations and also demonstrated a strong correlation between the concentration of iron in the growth medium and the production of biofilms by V. vulnificus.…”
Section: Factors Enhancing Biofilm Formation and Contaminationmentioning
confidence: 92%
See 1 more Smart Citation
“…To our knowledge, no recent studies have evaluated the impact of salt on the adhesion and formation of biofilms by V. vulnificus. On the other hand, the study by Velez et al (2023) showed higher biofilm production by several clinical and environmental strains of V. vulnificus and V. parahaemolyticus at acidic pH values. Çam and Brinkmeyer (2020) confirmed these observations and also demonstrated a strong correlation between the concentration of iron in the growth medium and the production of biofilms by V. vulnificus.…”
Section: Factors Enhancing Biofilm Formation and Contaminationmentioning
confidence: 92%
“…Mougin et al (2019) did not observe any difference in biofilm production of V. parahaemolyticus on stainless steel between 8 and 37 • C in three different media, but highlighted that V. cholerae exhibited greater survival at 8 • C rather than 37 • C, when cultivated in brine. Regarding V. vulnificus, it has been demonstrated that biofilm production by V. vulnificus cultured on glass and plastic is more significant at low temperatures (24-25 • C) than at high temperatures (35 and 37 • C) (Çam & Brinkmeyer, 2020;Leighton et al, 2022;Velez et al, 2023). In contrast, in their study of biofilms formed in glass tubes, Hernández-Cabanyero et al (2020) showed no significant difference in biofilm production at temperatures ranging from 20 to 37 • C, although a slight increase in biofilm quantity with increasing temperature was observed.…”
Section: Factors Enhancing Biofilm Formation and Contaminationmentioning
confidence: 99%
“…These two bacteria are most successful in environments with a pH level of 7.0-7.5, and their effectiveness decreases as the pH level drops. Bacterial cell membranes and enzymes are also at risk of being damaged by acidic seawater, reducing the bacteria's ability to cause harm [139][140][141].…”
Section: Ph-induced Oyster Diseasesmentioning
confidence: 99%